Biochemical Studies of Bacterial Sporulation and Germination XVII. Sulfhydryl and Disulfide Levels in Dormancy and Germination - Setlow, Peter (J Bacteriol, 1969)
A fourfold increase in sulfhydryl content upon germination of Bacillus megaterium spores was observed by the standard fluorescein mercuric acetate assay as reported by others. However, assay of ruptured dormant spores or the use of N-ethylmaleimide and a denaturing agent on intact spores showed a constant sulfhydryl level in dormancy and in germination. The apparent increase in sulfhydryl groups observed on germination was shown to be due to inaccessibility of most sulfhydryl groups in the dormant spore to sulfhydryl reagents. The disulfide content of dormant spores showed no change on germination, nor was any evidence found for production of low-molecular-weight sulfhydryl or disulfide compounds during germination.